Protective Effect of Sodium Nitroprusside on the Rat Small Intestine Transplanted Mucosa. (11th January 2015) - Chen, Feng-Hua; Li, Ke; Yin, Lu; Chen, Chun-Qiu; Yan, Zhao-Wen; Chen, Gui-Ming
Abstract : The intestinal mucosal epithelium is extremely susceptible to even brief periods of ischemia. Mucosal barrier damage, which is associated with ischemia/reperfusion (I/R) injury and consequently bacterial translocation, remains a major obstacle for clinically successful small bowel transplantation (SBT). Previous studies have demonstrated a protective effect of nitric oxide (NO) on other transplanted organs and NO mediated intestinal protection has also been reported in vitro . The aim of this study was to evaluate the effect of sodium nitroprusside (SNP), NO donor, on graft mucosal histology and molecular markers of function after SBT in rats. We used SNP in different period of heterotopic SBT rats. The groups consisted of SBT, pre-SNP group, and post-SNP group. Interestingly, the pre-SNP graft samples exhibited less damage compared to the SBT and post-SNP samples. In addition, mucosal samples from the pre-SNP group showed higher Na + -K + -ATPase activity and higher levels of laminin expression compared to the SBT and post-SNP samples. The findings of the present study reveal that SNP given before graft ischemia/reperfusion injury has a protective effect on mucosal histology and molecular markers of function in the transplanted small intestine.